Bimbingan dan Konseling - Nurhayati, Nurhayati; Sumiyati, Sumiyati; Juariyah, Juariyah; Paramitha, Paramitha; Syamsiah, Syamsiah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
Guidance teachers, also known as counselors, are responsible for providing guidance and counseling to students in schools by paying attention to the growth of the student's personality and abilities both physically and spiritually. able to live independently and fulfill their various responsibilities as God's creatures along with individual, social, moral, religious, and cultural creatures. Counseling is an effort to help people through a process of personal interaction between counselors and clients to help them understand themselves, their environment, make decisions, and set goals, so that they feel happy and behave well. Guidance Counseling plays an important role in educational institutions because it functions as a supporter of the progress or decline of the quality of education. The role of guidance and counseling in improving the quality of education is not only limited to academic guidance but also personal, social, intellectual guidance, and the provision of values. School guidance and counseling is also called school counselors/psychologists, Counselors play an important role in the education system, and they are considered school psychologists. Their counseling must include and have the aim of improving and expanding the potential of students. They must also have the ability to interact with the community and have interpersonal skills. Good society and alternative options for students. Planning, supervision, evaluation and follow-up of extension activities are carried out by extension workers. Extension workers are also responsible for informing students about career paths and solving their problems. Extension workers are given full freedom by the Minister of Education to develop students' potential and provide effective guidance and extension.